EVALUATING THE THERAPEUTIC IMPACT OF YOGIC PRACTICES ON RESPIRATORY DISEASES: A PILOT STUDY - Rubala Nancy. J; L. Ashwini; Anto Suganya. R; Devasena B; Kiran Kumar S (The Bioscan, 2025)
Yoga, a traditional Indian discipline that harmonizes body, mind, and spirit through physical postures, breathing exercises, and meditation, has gained global recognition for its therapeutic benefits. This pilot study assesses the role of yoga in managing respiratory health, focusing on its influence on pulmonary function and respiratory wellness. Participants engaged in a structured yoga program, including pranayama (breathing techniques) and asanas (postures), under guided supervision. Results indicated significant improvements in lung capacity, oxygen intake, and breathing efficiency, along with enhanced cognitive clarity, reduced stress, and bolstered immunity. The integrative practice of yoga demonstrated potential as a low-cost, non-invasive complementary therapy for individuals suffering from asthma, bronchitis, and other respiratory ailments. The study advocates the adoption of yoga-based interventions in public health strategies aimed at improving respiratory outcomes.